2002
DOI: 10.1063/1.1475627
|View full text |Cite
|
Sign up to set email alerts
|

Planck low frequency instrument

Abstract: -The Low Frequency Instrument (LFI) of the "Planck Surveyor" ESA mission will perform high-resolution imaging of the Cosmic Microwave Background anisotropies at four frequencies in the 30-100 GHz range. We review the LFI main scientific objectives, the current status of the instrument design and the on-going effort to develop software simulations of the LFI observations. In particular we discuss the design status of the PLANCK telescope, which is critical for reaching adequate effective angular resolution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The detector sensitivities of modern experiments have permitted to measure fluctuations of the CMB temperature with such a sensitivity that the contamination of the data by astrophysical foreground radiations, rather than by instrumental noise, is becoming the major source of limitation. This will be the case, in particular, for the upcoming observations by the Planck mission, to be launched by ESA in 2008 [Lamarre et al (2003), Mandolesi et al (2000), Lamarre et al (2000)], as well as for next generation instruments dedicated to the observation of CMB polarisation.…”
Section: Introductionmentioning
confidence: 99%
“…The detector sensitivities of modern experiments have permitted to measure fluctuations of the CMB temperature with such a sensitivity that the contamination of the data by astrophysical foreground radiations, rather than by instrumental noise, is becoming the major source of limitation. This will be the case, in particular, for the upcoming observations by the Planck mission, to be launched by ESA in 2008 [Lamarre et al (2003), Mandolesi et al (2000), Lamarre et al (2000)], as well as for next generation instruments dedicated to the observation of CMB polarisation.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a Poisson distribution of point sources in the sky, they found that the central frequency channels of the Planck mission will be 'clean' (i.e, only a few high latitude pixels will be contaminated by bright undetected sources). As for radio selected extragalactic sources, which contaminate CMB anisotropies at Planck Low Frequency Instrument (LFI) channels (Mandolesi et al 1998), their clustering signal was found to give a generally small contribution to temperature fluctuations, thanks to the broadness of the local luminosity function (Dunlop and Peacock 1990) and of the redshift distribution of sources which dilute the clustering signal (Toffolatti et al 1998Blake and Wall 2002). At higher frequencies, the clustering of far-IR selected dusty galaxies was found to give a more relevant -albeit not dominant -contribution to temperature anisotropies.…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider the constraints on w Q -Ω 0 that can be obtained from the analysis of the small scale CMB bispectrum for two experimental settings: the combination of MAP [4] and Atacama Cosmology Telescope (ACT; [5]), and the Planck surveyor satellite [6,7].…”
Section: Introductionmentioning
confidence: 99%